Enhanced biofilm formation and multi‐host transmission evolve from divergent genetic backgrounds in Campylobacter jejuni. (14th October 2015) - Pascoe, Ben; Méric, Guillaume; Murray, Susan; Yahara, Koji; Mageiros, Leonardos; Bowen, Ryan; Jones, Nathan H.; Jeeves, Rose E.; Lappin‐Scott, Hilary M.; Asakura, Hiroshi; Sheppard, Samuel K.
Summary: Multicellular biofilms are an ancient bacterial adaptation that offers a protective environment for survival in hostile habitats. In microaerophilic organisms such as C ampylobacter, biofilms play a key role in transmission to humans as the bacteria are exposed to atmospheric oxygen concentrations when leaving the reservoir host gut. Genetic determinants of biofilm formation differ between species, but little is known about how strains of the same species achieve the biofilm phenotype with different genetic backgrounds. Our approach combines genome‐wide association studies with traditional microbiology techniques to investigate the genetic basis of biofilm formation in 102  C ampylobacter jejuni isolates. We quantified biofilm formation among the isolates and identified hotspots of genetic variation in homologous sequences that correspond to variation in biofilm phenotypes. Thirteen genes demonstrated a statistically robust association including those involved in adhesion, motility, glycosylation, capsule production and oxidative stress. The genes associated with biofilm formation were different in the host generalist ST‐21 and ST‐45 clonal complexes, which are frequently isolated from multiple host species and clinical samples. This suggests the evolution of enhanced biofilm from different genetic backgrounds and a possible role in colonization of multiple hosts and transmission to humans.